Algunas características de las mareas en la costa Pacífica y Caribe de Centroamérica - Lizano R., Omar G. (Universidad de Costa Rica, 2009)
Tidal levels were studied in 48 stations using tidal predictions along the coasts of the Pacific and Caribbean of Central America. Statistics of basic mean values were analyzed to characterize the stations. These values are useful in coastal design structures as marines, ports, breakwaters, and for planning of marine operations in ports and piers. The tidal wave in the Pacific is simidiurnal, while in the Caribbean varies according to the latitude and the bathymetric basin in which it is found. In this last region the tidal wave can be mixed (a combination of semidiurnal and diurnal types) or semidiurnal pure. Some stations may show seasonal variations in the tidal wave according to the phases of the moon. It was found that the stations positioned in open coasts in the Pacific Ocean had smaller tidal range than those stations inside of semi-enclosed bodies of waters as bays and gulfs. Some stations in the interior of the Gulf of Panama showed very high tidal ranges associated possibly to resonance interactions of the tidal wave with the continental shelf and the geometry of the gulf. In the Caribbean Sea the tides seemed to resonance according to the basin and sea floor batimetry in which they are found. In some stations the oceanic and atmospheric forces as wind, atmospheric pressure, waves and currents, might generate the so called “weather tides” that could explain the major tidal range found in some of them.